Phytochrome and Seed Germination. III. Action of Prolonged Far Red Irradiation on the Germination of Tomato and Cucumber Seeds - Yaniv, Zohara (1967)
Prolonged irradiation with continuous or intermittent far red prevents the germination of tomato and cucumber seeds. The inhibitory efficiency of intermittent far red decreases with the lengthening of the interval between successive irradiations, and with the increase of temperature. If each far red irradiation is followed by red, germination is restored. Intermittent far red is less inhibitory than intermittent red-far red when red is given immediately before each far red. This effect is more evident when the interval between successive irradiation becomes longer.